My early years - Harrison, Paul (London, 1981)
Paul Harrison is a freelance writer and journalist based in London. He has travelled widely in Asia, Africa and Latin America, visiting twenty-seven developing countries. He writes regularly for the Guardian, New Society and the New Scientist, and for major development agencies such as the World Health Organization and the International Labour Office. Harrison attended Manchester Grammar School and Cambridge, where he got a double first in European literature and languages (of which he now speaks six). After a Council of Europe scholarship in Italy, he took a Masters in political sociology (with distinction) at the London School of Economics. His interest in the Third World began in 1968 while he was lecturing in French at the University of Ife, Nigeria. For the past ten years he has been in journalism. He is married, with two children, and is a part-time peasant on a small allotment with problematic soil.
Keywords: Agriculture